Understanding Environmental Transparency: A Study of Saudi Arabian Companies - Charchafa, Ilyes; Kimouche, Bilal (Oeconomica Jadertina, 2024)
This study explores the determinants of corporate environmental disclosure (CED) practices among listed companies in Saudi Arabia through an integrated agency theory and legitimacy theory lens. Drawing from a sample of 87 non-financial firms over 2015-2019, the analysis examines how corporate governance attributes like board size, board independence, and audit committee independence, as well as firm-specific characteristics including size, leverage, and international diversification influence the extent of  environmental disclosure. The findings reveal positive associations between CED levels and factors such as larger firm size, greater international presence, and operations in environmentally-sensitive industries. Conversely, increased leverage and surprisingly, larger board sizes exhibited negative relationships with disclosure extent. Board independence and audit committee independence showed no significant impact. To the best of the authors' knowledge, this represents the first investigation within the Saudi context examining the effects of audit committee independence and internationalization on CED. With a comprehensive set of explanatory variables and 435 firm-year observations, a larger-scale analysis is enabled compared to prior Saudi studies. By adopting the Global Reporting Initiative (GRI) environmental disclosure index, the study enhances comparability and precision in tracking CED trends over time. However, the study is limited by its reliance on annual report disclosures alone and the cross-sectional nature of the data. Future research could explore CED determinants through different theoretical lenses, such as stakeholder theory, institutional theory, and signaling theory, assess disclosure quality dimensions, and employ longitudinal panel analyses to provide further insights. The findings nonetheless underscore the need for stricter corporate governance regulations clarifying director independence criteria and sustainability reporting standards in Saudi Arabia to enhance transparency and environmental stewardship.
Keywords: Environmental disclosure; Environmental responsibility; Corporate governance; Company characteristics; Saudi Arabia